Competition kinetics of OH radical reactions with oxygenated organic compounds in aqueous solution: rate constants and internal optical absorption effects. Issue 16 (6th April 2018) - Schaefer, T.; Herrmann, H.
Abstract : Atmospheric aqueous phase rate constants are determined and the effect of optical absorbers in competition kinetics is studied. Abstract : Oxygenated organic compounds are omnipresent in the troposphere, due to their strong emissions from either biogenic or anthropogenic sources. Additionally, the degradation and oxidation processes of volatile organic compounds (VOCs) result in the production of oxygenated organic compounds in the troposphere. The degradation and conversion of these compounds are often initiated by radical reactions and occur in the gas phase as well as in the aqueous phase, including cloud droplets, fog, haze, rain or hygroscopic particles containing 'aerosol liquid water (ALW)'. In the present study, the temperature-dependent OH radical reactions with oxygenated organic compounds in the aqueous phase have been investigated by laser flash photolysis. To determine the rate constants, the OH radical – thiocyanate anion competition kinetics method has been used. Once the organic reactant has an absorption at the excitation wavelength of the photolysis laser, the initial OH concentration decreases. This internal absorption effect leads to an overestimated rate constant of the investigated compound. The present study considers this contribution in order to clarify the internal absorption effect of the investigated organic compounds. The following rate constants for OH radical oxidation reactions of the oxygenated organic compounds have been obtained: acetone (2-propanone) k 298K = (7.6 ± 1.0) × 10 7 L mol −1 s −1, 1-hydroxypropan-2-one k 298K = (1.1 ± 0.1) × 10 9 L mol −1 s −1, 1, 3-dihydroxypropan-2-one k 298K = (1.5 ± 0.1) × 10 9 L mol −1 s −1, 2, 3-dihydroxypropanal k 298K = (1.3 ± 0.1) × 10 9 L mol −1 s −1, butane-1, 3-diol k 298K = (2.5 ± 0.1) × 10 9 L mol −1 s −1, butane-2, 3-diol k 298K = (2.0 ± 0.1) × 10 9 L mol −1 s −1 and hexane-1, 2-diol k 298K = (4.6 ± 0.4) × 10 9 L mol −1 s −1 . With the rate constants obtained and their T-dependencies, the source and sink processes of oxygenated organic compounds in the tropospheric aqueous phase are arrived at precisely. These findings might enhance the predictive capabilities of models such as the chemical aqueous-phase radical mechanism (CAPRAM).